Spatial controls of methane uptake in upland soils across climatic and geological regions in Greenland - Ludovica D’Imperio; Bing-Bing Li; James M. Tiedje; Youmi Oh; Jesper Riis Christiansen; Sebastian Kepfer-Rojas; Andreas Westergaard-Nielsen; Kristian Koefoed Brandt; Peter E. Holm; Peiyan Wang; Per Ambus; Bo Elberling (Communications Earth & Environment, 2023)
Abstract In the Arctic, the spatiotemporal variation of net methane uptake in upland soils depends on unresolved interactive controls between edaphic and microbial factors not yet included in current models, underpinning the uncertainty of upscaling the Arctic methane budget. Here we show that upland soils in Greenland are consistent methane sinks (−1.83 ± 0.19 nmol methane g−1 dw d−1) across a N-S (64–83 °N) pedoclimatic transect. We demonstrate that methane oxidizers abundance, soil pH, and available soil copper are important controls on the spatial variation in methane oxidation. We revised a soil biogeochemical model with a high-resolution land classification and meteorological data for Greenland and tested it against our methane uptake measurements. The model simulated well the magnitudes of observed methane uptake but not the spatial variation across all sites. This work provides novel insights into the controls of methane uptake, which are critical for the accuracy of methane budgets.